PENATAAN ARSIP PADA KANTOR DESA NEGERI LARIKE - Siti Jainab Latuapo; Grace Fredriksz; Febiyola Wijaya (Jurnal Administrasi Terapan, 2023)
Archive management at the Larike Village Office is not very good in the sense that the archives have not been stored, recorded, documented and neatly arranged so that when needed it takes 15 minutes while searching for archives is approximately 1 minute. The filing facility at the Larike Negeri Village office is 1 cupboard in which there are folders. The employee only records outgoing letters in the agenda book and does not record incoming letters, but the recording is still not correct and after recording the employee places the letters on the employee's desk, there is also a wooden cupboard. This makes the letters are not archived properly, easily scattered and lost. When the leader asks for a letter, his employees have difficulty finding the letter back. The purpose of this writing is to find out about good archive management at the Larike Village office. The method used in this paper is qualitative analysis, that describe problems based on theories and expert opinions. The results of the discussion are providing input or solutions regarding the arrangement of archives using an alphabetic system, so that it can facilitate the search or retrieval of archives, employees must attend archiving training. The conclusion of this study the archive management system at the Larike Village office was not very good because it was not in accordance with existing procedures. Archive storage facilities are inadequate. Employees who handle archives have not attended archiving training so that the arrangement of archives at the Larike Village office is irregular in accordance with existing provisions Keywords: management, archive, office